Modeling personality antecedents and second language self-efficacy constructs with emerging adults in Japan: Domain-specific matching for assessing global competence in applied contexts - Kabir, Russell Sarwar; Kramer, Brandon; Koike, Mayu; Sponseller, Aaron C. (Frontiers in Psychology, 2022)
Introduction Research on self–efficacy in intercultural communication (SEIC) provided validity evidence for second language (L2) self-efficacy domains. However, it lacked (1) an analysis of individual differences in personality as antecedents, (2) divergent validity from anxiety variables (i.e., foreign language classroom anxiety; FLCA), and (3) disambiguation from speaking (S-SE) and listening (L-SE) skill-specific self-efficacy types. Methods We conducted structural equation modeling of L2 self-efficacy and anxiety as response variables predicted by the Big Five model of personality in the context of Japanese undergraduate students at three university sites (n = 373), and a geographically diverse online survey of emerging adults (n = 1,326) throughout Japan. Results The final model for the nationally representative sample showed that SEIC was predicted by all identified personality factors. Differentially supported paths were observed linking L-SE with Conscientiousness (β = 0.24) and Extraversion (β = 0.16), and S-SE with Extraversion (β = 0.24) and Neuroticism (β = −0.12). The fear of failure factor of FLCA was predicted positively by Neuroticism (β = 0.25) and, surprisingly, Conscientiousness (β = 0.10), and negatively by Extraversion (β = −0.13). Relationships to Openness to Experience were only supported for SEIC (β = 0.17) and S-SE (β = 0.12). Discussion These findings provide specificity matching for personality and L2 self-efficacy domains as empirical advances for assessing global competence within the context of Japan. Implications for cultural influences on self-efficacy and applied educational practices in language and intercultural learning are discussed.